2012
DOI: 10.1111/j.1365-2710.2012.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-steroidal anti-inflammatory drugs on antiplatelet effect of aspirin

Abstract: What is known and Objective: It has been reported that ibuprofen interferes with the antiplatelet effect of low-dose aspirin. This interaction is ascribed to steric hindrance at the active site of cyclooxygenase-1 by ibuprofen, when aspirin is administered after ibuprofen. However, whether other nonsteroidal anti-inflammatory drugs (NSAIDs) interact with aspirin similarly is not well defined. The aim of this study was to assess the influence of nine NSAIDs on the antiplatelet effect of aspirin. Methods: We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
(10 reference statements)
1
11
0
2
Order By: Relevance
“…This observation is consistent with the result of a similar study on aquatic animals [30]. Although, NSAIDs are known to have antiplatelet activities [10], the antiplatelet effects of ibuprofen in relation to dose and duration of exposure is not fully established. Our observation of the reduction of platelet counts after 14 and 28 days of ibuprofen exposure, and a non-effect after 7 days of exposure in this study, strongly suggests that the antiplatelet effect of ibuprofen is more important with duration of exposure than dose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with the result of a similar study on aquatic animals [30]. Although, NSAIDs are known to have antiplatelet activities [10], the antiplatelet effects of ibuprofen in relation to dose and duration of exposure is not fully established. Our observation of the reduction of platelet counts after 14 and 28 days of ibuprofen exposure, and a non-effect after 7 days of exposure in this study, strongly suggests that the antiplatelet effect of ibuprofen is more important with duration of exposure than dose.…”
Section: Discussionsupporting
confidence: 93%
“…However, most of such reports are on high dose levels of the agents (> clinical doses) and existing data on ibuprofen-mediated renal toxicity in relation to duration of exposure is not exhaustive. Furthermore, NSAIDs are known to have antiplatelet activities [10], however, the antiplatelet effects of ibuprofen in relation to dose and duration of exposure is not fully established. Importantly, ibuprofen is an over-the-counter NSAID, with the consequence of an increase in its usage and toxicological potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the previous in vitro studies, this study found that both flurbiprofen and naproxen caused substantial inhibition on aspirin's antiplatelet effects, whereas other NSAIDs, such as diclofenac, had insignificant effects on aspirin's antiplatelet activity regardless of administration time. 13 These studies are in vitro in nature and do not establish whether this interaction exists in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Ibuprofen and naproxen, but not etoricoxib or meloxicam, taken 2 h before aspirin, significantly inhibited the aspirin effect. In another study, Yokoyama et al tested nine NSAIDs (loxoprofen, ibuprofen, diclofenac, naproxen, mefenamic acid, flurbiprofen, indomethacin, etodolac and meloxicam) [18]. They concluded that ibuprofen and mefenamic acid reduced platelet aggregation when given before aspirin.…”
Section: Ex Vivo Studiesmentioning
confidence: 96%